Pengaruh Implementasi Kurikulum Berbasis Iduka Terhadap Peningkatan Kompetensi Siswa di SMKN 5 Sijunjung - Antonio Reinaldo (Program Studi Manajemen Pendidikan Islam, 2024)
This study aims to determine: (1) the context of the IDUKA Program (Link and Match), including (a) the quality of student competencies, (b) policies and objectives of the IDUKA Program (Link and Match), (c) readiness for the management of the IDUKA Program. (Link and Match) The results show: (1) Evaluation of the context of the IDUKA program is high. This aspect consists of: (a) The quality of the students competencies. (b) The conformity of the implementation of the IDUKA program with the policies and objectives set by the school. (c) The readiness of the implementation management carried out by the school is classified as high. Keywords: IDUKA Curriculum, Student Competencies